Phenotypic variation among IR64 × TOG5681 rice (Oryza sativa × O. glaberrima) chromosome segment substitution lines (CSSL) in response to iron toxicity, and its associated QTLs - Sikirou, M.; Drame, K.N.; Saito, K.; Bocco, R.; Lorieux, M. (2025)
Iron (Fe) toxicity presents a significant challenge to rice production in lowland ecosystems globally. The identification of genetic factors responsible for Fe toxicity tolerance is crucial for the development of tolerant rice varieties. This study aimed to unravel the genetic bases of Fe toxicity tolerance using quantitative trait locus (QTL) mapping. We conducted phenotypic evaluations for Fe toxicity tolerance on 54 chromosome segment substitution lines (CSSLs) obtained from a cross between the moderately susceptible IR64 (O. sativa) and the tolerant donor TOG5681 (O. glaberrima) under Fe toxicity stress. QTL analysis was performed using agro-morphological traits and microsatellite genotypic data. We observed high heritability estimates for key traits like leaf bronzing score (LBS) and grain yield. Several loci associated with agronomic traits, including plant height (qPH2.1), panicle number (qPN4.1), grain weight (qGW4.1), harvest index (qHI4.1), maturity (qMat6.1), and shoot weight (qSW6.1 and qSW11.1), were identified. From the field experiments, three CSSL lines (CCSLOG254, CCSLOG255, and CCSLOG256) that exhibit both high yield and tolerance to iron toxicity have been identified, positioning them as promising candidates for breeding programs. Additionally, a major QTL (qLBS11.1) linked to leaf bronzing (LBS) was identified, housing the OsbHLHq11 gene involved in iron homeostasis regulation. A comparative analysis revealed colocation with previously reported QTLs, validating their significance. OsbHLHq11 was found to be conserved across diverse rice germplasm, including lowland NERICA (NEw RICe for Africa) varieties, which were developed through crossing O. sativa and O. glaberrima. The discovery of qLBS11.1 and the candidate gene OsbHLHq11 offers insights into the genetic mechanisms governing Fe toxicity tolerance, highlighting potential targets for breeding tolerant rice varieties using marker-assisted selection or genetic engineering strategies.